Development of a low carbon lifestyle predictive model in Putrajaya, Malaysia - Mohamed, Azalia (2017)
This research examined low-carbon lifestyle adoption in the quest to understand why the public have not enthusiastically taken up this new lifestyle. Putrajaya was chosen as the location of the study because it is Malaysia’s pioneer low-carbon city, a model city that embraces the concept of sustainable development with a goal of reducing carbon footprint in all aspects of urban living. The population chosen for this study was leaders of residents’ association committees (RACs) whom are most knowledgeable about the community and their issues.